Geomorphological analysis of the Usumacinta and Grijalva sub-basins in southeastern Mexico - Castillo Cruz , Zayra Guadalupe; Medrano Pérez, Ojilve Ramón (Acta Universitaria, 2023)
Watersheds integrate a series of processes and environmental characteristics that are expressed in the morphometry of drainage networks. Morphometric analysis is key to understanding the functioning of the hydrological system of a basin. Its use is practical in areas with limited climatological information and a lack of knowledge about the functioning of the hydrological system. The main objective of this work is to characterize the geomorphology of the Grijalva and Usumacinta sub-basins in southeastern Mexico using geographic information systems (GIS) and a series of morphometric parameters associated with general characteristics, relief, drainage network, and the form of these sub-basins to analyze and understand hydromorphological behavior. The results obtained show some contrast between both basins around the parameter of the number of runoffs, which has implications in terms of energy and the capacity and magnitude of water collection of the sub-basin and the river network of both sub-basins. In this context, it is expected to contribute to local knowledge and the strengthening of decision-making in the areas of territorial planning, civil protection, infrastructure, and public policies.